Validation of the German version of the Driver Skill Inventory (DSI) and the Driver Social Desirability Scales (DSDS). (February 2017) - Ostapczuk, Martin; Joseph, Robin; Pufal, Janine; Musch, Jochen
Highlights: The German DSI and DSDS were validated in more than 1000 car drivers. Both inventories proved reliable and showed the expected 2-factor structure. Convergent and discriminant validity were established for both inventories. The German DSI is not contaminated by social desirability to an appreciable extent. Abstract: The psychometric properties of the new German versions of the Driver Skill Inventory (DSI) and the Driver Social Desirability Scales (DSDS) were examined. The DSI is a self-report measure assessing perceptual-motor skills and the safety motive as two important aspects of driving behavior. Self-report measures, however, are susceptible to socially desirable responding (SDR) which is why both general and specific driving-related SDR scales have been developed: Based on the Balanced Inventory of Desirable Responding (BIDR), the DSDS taps Driver Impression Management and Driver Self-Deception as two important aspects of SDR. In two validation studies with less experienced ( N  = 130) and experienced drivers (N = 1199), both inventories showed the expected two-factor structure and satisfactory internal consistency. In Study 1, self-ratings were compared with and confirmed by peer-ratings. In both studies, we accumulated evidence of convergent and discriminant validity for the German version of the DSI by correlating it with demographic, driving-specific, and personality measures, including the Big Five, Type A behavior, and sensation seeking. The DSI seemed to be only marginally contaminated by SDR.